SYSTEMATIC LITERATURE REVIEW: PEMBELAJARAN PECAHAN MENGGUNAKAN PENDEKATAN PENDIDIKAN MATEMATIKA REALISTIK INDONESIA - Sukasno, Sukasno; Zulkardi, Zulkardi; Putri, Ratu Ilma Indra; Somakim, Somakim (LP4MK STKIP PGRI Lubuklinggau, 2023)
This study aims to conduct a literature review related to fractional learning with the Indonesian Realistic Mathematics Education (PMRI) approach. The method used is Systematic Literature Review (SLR). The articles that were used as a source of review in this study were 9 articles related to the application and development of the PMRI approach to the material of fractions in the period 2017-2021. Articles come from reputable journals and are indexed by sinta and proceedings are indexed by scopus. From the results of the review, it was found that there were problems related to learning outcomes, understanding concepts, and the learning process on the material of fractions. The application and development of learning with the PMRI approach has a positive impact on the development of students' conceptual understanding of the fractional number material. Through the PMRI approach, students can develop fun learning situations, because learning activities are oriented to everyday concrete situations. The use of concrete media gives a good contribution in developing students' conceptual understanding of the fraction material. The developed learning trajectory can lay an important foundation in helping the development of the concept of fractions.